PENGARUH TERPAAN KAMPANYE DAN PERSEPSI GIMMICK “ULTRAMAN” TERHADAP KETERPILIHAN ANGGOTA LEGISLATIF JAMALUDIN MALIK PERIODE 2024-2029 - Nesya Shafa Nabila Wardani; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2026)
The political campaign using an Ultraman costume gimmick by legislative candidate Jamaludin Malik in the 2024 election became a unique phenomenon that attracted public attention. Massive campaigns were carried out both conventionally and non-conventionally. Such a political marketing style raised assumptions regarding the influence of campaign exposure and voter perception of his political marketing in shaping voting behavior. The purpose of this study is to examine whether the Ultraman gimmick campaign exposure and voter perception simultaneously influence the electability of Jamaludin Malik. This study uses S-O-R theory and the Elaboration Likelihood Model with an explanatory quantitative method. The sample in this study was determined using purposive sampling technique with the criteria of voters in Jepara Regency totaling 100 respondents who had received exposure to information about the Ultraman campaign of Jamaludin Malik, particularly on social media. Data analysis used binary logistic regression because the dependent variable is categorical. The results showed that Ultraman gimmick campaign exposure (X1) had a significant effect on voting decisions with an odds ratio of 1.365, meaning that every increase in campaign exposure increases the probability of choosing Jamaludin Malik by 1.365 times. Meanwhile, voter perception (X2) had no significant effect in the partial test. However, simultaneously, both variables were proven to have a significant effect on voting decisions with a chi-square value of 37.151. The independent variables were able to contribute an effect of 41.9% on voting decisions. These findings indicate that voters tend to process campaign messages through the peripheral route, which emphasizes visual and emotional appeal more dominantly than the central route in shaping voting decisions.